ILRI Kapiti Wildlife Conservancy: Conservation Management Plan 2022-2026 - Sircely, Jason; Gluecks, Ilona; Gerba, Michael (International Livestock Research Institute, 2022)
The ILRI Kapiti Wildlife Conservancy is among the foremost areas in Africa for research on livestock production and climate change affecting the environment, livestock and wildlife of the rangelands in Kenya, East Africa, and the world. Research produced at the ILRI Kapiti Wildlife Conservancy supports the livestock sector in Kenya and throughout the continent, by providing jobs, economic growth, and a pathway out of poverty for smallholder farmers. The conservancy is also dedicated to protecting the biodiversity of the Athi-Kapiti ecosystem’s dispersal areas that enable the movement of wildlife from the Nairobi National Park to the Amboseli, Tsavo and eventually the Mara-Serengeti ecosystems. This management plan is a living document that provides an overview for 2022-2026.